Features of urging hashtags during the period of the Revolution of Dignity - Сопіна, Катерина Вячеславівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article considers the features of urging hashtags that functioned in Facebook and Twitter social networks during the Euromaidan. The role of hashtags in times of revolutions has been identified, and it has been noted that hashtags help uncensored revolutionaries to disseminate information among their compatriots and the world community, attract the attention of the world media, and encourage people to support and join them. The paper considers syntactic features of urging hashtags, it is indicated that in the vast majority of cases such hashtags are located at the end of the post, although some may be located in the middle of the post. In addition the paper mentions publications consisting of some hashtags, among which are urging hashtags. Studying urging hashtags as sentences, the author singled out the following types: simple and complex, two-syllable and one-syllable, common and uncommon, complete and incomplete, complicated and non-complicated. Moreover, it has been noted that urging hashtags have a motivating modality. In regards of the peculiarities of the graphics of urging hashtags, the author points out the difference in spelling of the same words to create a different visual effect. Due to the fact that the hashtags use no spaces, the addressers wrote the sentence in one word, and in order to visually separate the words, the beginning of a word was capitalized or words were hyphenated. In addition, attention is drawn to punctuation and apostrophes: authors did not use those in the posts, because they „break” the words, after which the statement ceases to be the one single hashtag. In order to spread urging hashtags not only in the Ukrainian-speaking space, but also among the world audience, the addressers published urging hashtags in both Ukrainian and English, while the use of urging hashtags in Ukrainian remains more frequent.